Information technology (IT) in agriculture sector: issues and challenges / Nurul Hanis Azrin Sabirin, Noor Fadzlina Mohd Fadhil and Juliana Arifin - Sabirin, Nurul Hanis; Mohd Fadhil, Noor Fadzlin; Arifin, Juliana (Research Management Institute (RMI), 2022)
Agriculture is the backbone of food production in every nation and the central element in economic development. Rapid changes in information technology (IT) have promised substantial potential benefits in return, especially for developing countries. The success of IT applications in agriculture is widely reported in numerous previous studies. Regardless of its success, the transformation has brought many issues and challenges for farming businesses. Thus, this article aimed to review the major issues and challenges of IT usage and how technology resources can address the needs of demand for food production. The findings reveal three main themes of issues and challenges, which are infrastructure, people, and organisation. Due to these issues, there is a greater need for changes in IT resources in agriculture to meet the food demand for the rapid growth of the population by the year 2050. A systematic review using existing literature has been used in writing this article.